The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph182111645
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Effects between Continuous and Intermittent Energy Restriction in Short-Term Bodyweight Loss for Sedentary Population: A Randomized, Double-Blind, Controlled Trial

Abstract: Objective: To compare the effects of continuous energy restriction (CER) and intermittent energy restriction (IER) in bodyweight loss plan in sedentary individuals with normal bodyweight and explore the influence factors of effect and individual retention. Methods: 26 participants were recruited in this randomized controlled and double-blinded trial and allocated to CER and IER groups. Bodyweight (BW), body mass index (BMI), and resting metabolic rate (RMR) would be collected before and after a 4-week (28 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…In terms of time effects, a 4-week dietary restriction combined with HIIT intervention could significantly reduce in body weight, BMI, BF%, WC, and HC. This phenomenon is consistent with the results of studies outlined previously in which dietary restriction was used only for 4-week (43). The present data showed that the reduction in body weight in the iER, cER, and ND groups was 4.6, 2.5, and 1.4, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In terms of time effects, a 4-week dietary restriction combined with HIIT intervention could significantly reduce in body weight, BMI, BF%, WC, and HC. This phenomenon is consistent with the results of studies outlined previously in which dietary restriction was used only for 4-week (43). The present data showed that the reduction in body weight in the iER, cER, and ND groups was 4.6, 2.5, and 1.4, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Recent systematic reviews conclude that IER tended to decrease more body weight and fat mass in comparison to CER in overweight or obese subjects ( 52 ), it is superior in terms of improving lipid metabolism, resulting in a greater loss of body fat ( 8 , 10 ). In the work of Xu et al both IER and CER interventions could resulted in the body weight and BMI to be significantly lower in sedentary individuals, but without a significant difference between groups following a 4-week intervention ( 43 ). Our findings demonstrated that under the conditions of HIIT, the iER group had a greater reduction in body weight, BMI, BF%, WC, and HC compared to the cER group, but there was no significant difference between the groups.…”
Section: Discussionmentioning
confidence: 99%